2003
DOI: 10.1124/jpet.103.057943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Different A1Adenosine Receptor Antagonists on Infarct Size and Multiple Cycle Ischemic Preconditioning in Anesthetized Dogs

Abstract: A 1 adenosine receptor (AR) antagonists are effective diuretic agents that may be useful for treating fluid retention disorders including congestive heart failure. However, antagonism of A 1 ARs is potentially a concern when using these agents in patients with ischemic heart disease. To address this concern, the present study was designed to compare the actions of the A 1 AR antagonists CPX (1,3-dipropyl-8-cyclopentylxanthine), BG 9719 (1,3-dipropyl-8-[2-(5,6-epoxynorbornyl)]xanthine), and BG 9928 (1,3-dipropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…That study demonstrated that inhibition of A 1 AR during reperfusion diminished infarct size (IF) and regional myocardial dysfunction after I/R (8). Another study in anesthetized dogs (2) further supported this theory by demonstrating that pretreatment with either of two A 1 AR antagonists (DPCPX and BG-9928) before ischemia decreased IF after regional left arterior descending coronary artery (LAD) occlusion (2). That study also demonstrated that pretreatment with three different A 1 AR antagonists failed to prevent IF reduction by IPC (2).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…That study demonstrated that inhibition of A 1 AR during reperfusion diminished infarct size (IF) and regional myocardial dysfunction after I/R (8). Another study in anesthetized dogs (2) further supported this theory by demonstrating that pretreatment with either of two A 1 AR antagonists (DPCPX and BG-9928) before ischemia decreased IF after regional left arterior descending coronary artery (LAD) occlusion (2). That study also demonstrated that pretreatment with three different A 1 AR antagonists failed to prevent IF reduction by IPC (2).…”
supporting
confidence: 54%
“…Another study in anesthetized dogs (2) further supported this theory by demonstrating that pretreatment with either of two A 1 AR antagonists (DPCPX and BG-9928) before ischemia decreased IF after regional left arterior descending coronary artery (LAD) occlusion (2). That study also demonstrated that pretreatment with three different A 1 AR antagonists failed to prevent IF reduction by IPC (2). The discrepancy between all of the above findings may be due to differences in the selectivity of the antagonists for multiple adenosine receptor subtypes.…”
mentioning
confidence: 99%
“…However, BG9719 contains an epoxide group, which is potentially chemically reactive. However, a non-epoxide-containing antagonist in the same series, BG9928, improves renal function and congestive heart failure without exacerbating cardiac injury 161 . BG9928, now in Phase II clinical trials, was found to improve sodium excretion in heart failure patients.…”
Section: Ars As Targets In Renal System Disordersmentioning
confidence: 99%
“…Additional reports support the hypothesis that adenosine receptor subtype interactions may occur in the heart. Sympathetic nerve-mediated coronary constriction in stunned canine myocardium is induced by the infusion of a combination of adenosine A 1 and A 2a agonists but not by either agonist alone (3). It has been reported that cardiac adenosine A 2a receptors modulate the adenosine A 1 receptor anti-adrenergic effect (22,34).…”
mentioning
confidence: 99%